2020
DOI: 10.1016/j.ejmech.2020.112621
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel small molecule inhibitors of S100P with in vitro anti-metastatic effects on pancreatic cancer cells

Abstract: S100P, a calcium-binding protein, is known to advance tumor progression and metastasis in pancreatic and several other cancers. Herein is described the in silico identification of a putative binding pocket of S100P to identify, synthesize and evaluate novel small molecules with the potential to selectively bind S100P and inhibit its activation of cell survival and metastatic pathways. The virtual screening of a drug-like database against the S100P model led to the identification of over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…S100A2/A10 have recently been suggested as negative prognostic biomarkers for pancreatic cancer ( Bachet et al, 2013 ; Bydoun et al, 2018a ). S100P/A11 are unfavorable to the prognosis of PAAD patients undergoing surgical resection ( Xiao et al, 2012 ; Camara et al, 2020 ). Collectively, the clinical significance of S100s members and their potential application in the development of PAAD have been highlighted, although their predictive potential and biological characteristics need to be further validated.…”
Section: Introductionmentioning
confidence: 99%
“…S100A2/A10 have recently been suggested as negative prognostic biomarkers for pancreatic cancer ( Bachet et al, 2013 ; Bydoun et al, 2018a ). S100P/A11 are unfavorable to the prognosis of PAAD patients undergoing surgical resection ( Xiao et al, 2012 ; Camara et al, 2020 ). Collectively, the clinical significance of S100s members and their potential application in the development of PAAD have been highlighted, although their predictive potential and biological characteristics need to be further validated.…”
Section: Introductionmentioning
confidence: 99%
“…Ramatoulie Camara et al used in silico methods to identify potential binding pockets in the NMR ensemble of S100P and successfully discovered several small molecule inhibitors that affect the S100P-RAGE interaction and S100P-mediated cell invasion, which can inhibit S100P-expressing PC cell invasion in vitro. This provides strong evidence of the potential of S100P inhibitors as chemotherapeutics for PC (159). In addition, through in vitro cell experiments and using mouse models, it has been found that cromolyn may bind to S100P to prevent activation of RAGE, thereby inhibiting S100P-mediated PC growth, survival and invasiveness (145).…”
Section: Othersmentioning
confidence: 86%
“…S100P, a calcium-binding protein, can advance tumor progression and metastasis in pancreatic and several other cancers ( 6 , 30 , 31 ). S100P has previously been demonstrated to regulate the proliferation, migratory and invasive capabilities of PAAD cells ( 6 ).…”
Section: Discussionmentioning
confidence: 99%